Dietary sodium and potassium intake were associated with hypertension, kidney damage and adverse perinatal outcome in pregnant women with preeclampsia - Zehra Vural Yılmaz; Elif Akkaş; Gülenay Gençosmanoğlu Türkmen; Özgür Kara; Aykan Yücel; Dilek Uygur (Taylor & Francis Group, 2017)
Objectives: In this study, we hypothesized that dietary salt and potassium intake may be related with blood pressure, kidney damage and perinatal outcome in pregnants with preeclampsia (PE). Methods: In total, 200 women (50 control women with healthy pregnancy, 150 women with PE) were recruited for the study. Daily salt and potassium intake was estimated based on calculation of 24-hour urinary sodium U[Na+] and potassium U[K+] excretion. U[Na+]/[K+] was calculated by dividing U[Na+] by U[K+]. At the end of the measurements, the pregnant women with PE (n=150) were divided into tertiles according to U[Na+]/[K+]: low Na/K group (n=50, mean U[Na+]/[K+]: 1,04±0,32), medium Na/K group (n=50, mean U[Na+]/[K+]: 2,49± 0,54), high Na/K group (n=50, mean U[Na+]/[K+]: 6,62±3,41). Results: The mean SBP and DBP levels were significantly lower in low Na/K group compared with medium or high Na/K groups (p=0.024, p=0.0002; respectively). Serum creatinine was significantly lower in low Na/K group than high Na/K group (p=0.025). Frequency of severe preeclampsia is lower in low Na/K group than medium or high Na/K groups (p=0.002, p=0.0001; respectively). Birth weight and gestational age at birth were higher in low Na/K group compared with high Na/K group (p=0.045, p=0.0002; respectively). After adjusting for covariates, SBP and DBP and creatinine levels were independently associated with 24 hours urinary [Na+]/[K+] Conclusion: These findings suggest that pregnant with PE with high dietary salt and low potassium intake may have greater maternal and neonatal morbidity risk than pregnant with PE under low dietary salt and high potassium intake.